SPEAKING SKILL IN TEFL: HOW SHORT DIALOGUE PLAYS ITS ROLE - Muti'ah, Fina; Aswir, Aswir (Jurnal Kajian Pembelajaran dan Keilmuan, 2024)
This research was aimed to examine the impact of "˜Short Dialogues"™ in students"™ speaking improvement. The researchers conducted this study on 2023/2024 academic year at Pondok Pesantren Tahfidzul Quran Nurul Furqon in Bintaro, Jakarta, Indonesia. There was one class of 7 graders participated in this study, occupied by 26 students. This study employed quantitative pre-experimental method with one group pre-test and post-test approach. Thus, speaking pre- and post-tests were used as the instruments to collect the data. These data were analyzed statistically by using paired-sample t-test. The quantitative computation revealed that the students gained higher speaking performance in the post-test than in the pre-test in which on average, they gained 85 score in the post-test while in the pre-test was 43.26. To be put into speaking categories, majority of the students were in "˜poor"™ level (73.68%) in the pre-test and most of them were in "˜good"™ level (61.54%) in the post-test. Statistically, paired-sample t-test resulted significance value of .001, or lower than 0.05, indicating that the difference gained by the students in terms of their speaking achievement in the two tests was affected by the employment of Short Dialogues technique. Thus, this research concluded that Short Dialogues played an effective role in improving students"™ speaking skill.